The Effect of Service Quality and Price Strategy on Customer Satisfaction through Purchasing Decisions as an Intervening variable In 212 Mart Gowa, South Sulawesi Province - Afra Nurul; Otto Randa Payangan; Muhammad Ismail (Magister Management, Hasanuddin University, 2020)
Along with the development of increasingly modern times, this has caused a lot of competition in the business world, including retail business. Every businessman needs to pay attention to the factors that influence customer purchasing decisions. The research objective is to determine the effect of service quality and pricing strategies on purchasing decisions, determine the effect of service quality and pricing strategies on customer satisfaction, determine the effect of purchasing decisions on customer satisfaction, to determine the effect of service quality and price strategies on customer satisfaction through purchasing decisions at 212 Mart Gowa The population in this study were all consumers who shop at 212 Mart Gowa determined as many as 100 respondents. Data collection techniques through observation, interviews, and questionnaires. While the data analysis technique uses validity and reliability, path analysis, hypothesis testing, and coefficient of determination. The results of the study found that service quality has a positive but not significant effect on purchasing decisions, price strategy has a positive effect but is not significant on purchasing decisions, service quality has a positive and significant effect on customer satisfaction, price strategy has a positive and significant effect on customer satisfaction, purchasing decisions have a positive effect and significant on customer satisfaction, service quality has a positive but not significant effect on customer satisfaction through purchasing decisions, and the price strategy has a positive but not significant effect on customer satisfaction through purchasing decisions on 212 Mart Gowa.